Process optimization and quality perceived by passengers: the case study of Lisbon Airport - Sousa, Filipe Miguel Corales de Oliveira (2019)
Increasing demand due to the banalization of air traffic as preferred means of transport, by the globalization of business and tourism, and by the speed of air transportation, has made airports the answer to this massive influx of people around the World. The following case study aims to show professionals and students in Operations Management areas the need to look at customers as part of the operational process. Thus, to provide a higher quality service, it is necessary to look at the processes and coordination of the various links in the service chain, so that the system is as fluid and optimized as possible. Thus, the case study will show the Lisbon Airport case, an airport that have a substantial growth on the last five years. It will show what operational strategies that were implemented so that the customer service provision does not be harmed by maintaining quality levels and parameters. To explain the situation of Lisbon Airport, was made a case study. The case study will have the focus on showing the relevant key performance indicators, the stakeholders involved in the process, the flow of passengers through the infrastructure and the changes done in the airport. For the literature review was done an analysis on operations management, quality of service and service design. This case study aims to be studied by undergraduate or master students in the area of Operations Management. To consolidate knowledge was developed a set of questions applied to the case of Lisbon Airport.